Charge Storage and Solar Rechargeable Battery Devices Based on Electrodes Electrochemically Modified with Conducting Polymer Nanowires - Gacitua-Santalices, M; Gacitua-Santalices, M (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In this work, the use of nanostructured conducting polymer deposits on energy-storing devices is described. The cathode and the anode are electrochemically modified with nanowires of polypyrrole and poly(3,4-ethylenedioxythiophene), respectively, prepared after the use of a mesoporous silica template. The effect of aqueous or ionic liquid medium is assayed during battery characterization studies. The nanostructured device greatly surpasses the performance of the bulk configuration in terms of specific capacity, energy, and power. Moreover, compared with devices found in the literature with similar designs, the nanostructured device prepared here shows better battery characteristics, including cyclability. Finally, considering the semi-conducting properties of the components, the device was adapted to the design of a solar-rechargeable device by the inclusion of a titanium oxide layer and cis-bis(isothiocyanate)-bis(2,2′-bipyridyl-4,4′-dicarboxylate) ruthenium (II) dye. The device proved that the nanostructured design is also appropriate for the implementation of solar-rechargeable battery, although its performance still requires further optimization. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.